Comparison between an Innovative Solarization System and Dazomet-Based Fumigation - Massimo Rippa; Changrong Yan; Qin Liu; Elia Tucci; Pasquale Mormile (Soil Systems, 2023)
An innovative soil solarization system based on biochar was recently proposed. The difference with traditional solarization lies in the use, after soil irrigation, of a biodegradable black liquid sprayed on the soil surface in order to obtain a black body capable of drastically increasing the absorption of incident radiation and, as a consequence, increasing temperatures at different depths. Due to these higher temperatures, it is possible to eliminate pathogens in shorter times than with traditional solarization. In recent years, this practice has been tested in various contexts by comparing traditional solarization with this innovative new practice through temperature measurement at different soil depths for two months. The experimental data confirm the validity of this new approach for soil treatment: higher temperatures were registered with the innovative system, up to 10 °C more than the traditional method. In this work, we report a comparison between the new solarization system and a fumigation method. Our experimental results demonstrate that it is possible to obtain a satisfying soil treatment with a natural and sustainable practice based on solar energy, overcoming the major limitation of traditional solarization: application time. The black layer on the soil allows for the attainment of temperatures as high as necessary to eliminate most pathogens in a shorter time (just 30 days) than traditional solarization (2 months).